YouTube as a Platform for an Online Dialogic ESL Teaching and Learning / Anis Shaari and Berlian Nur Morat - Shaari, Anis; Nur Morat, Berlian (Universiti Teknologi MARA, Kedah, 2016)
Having the ability to communicate has been such a crucial aim in the teaching and learning of ESL. Nevertheless, in reaching the target, the ESL context has encountered various issues concerning individual differences. These include learners’ personalities, motivation as well as learning styles and strategies. Questions have emerged whether the introverts and the less motivated ESL learners really learn the language, particularly in terms of the ability to communicate using English. It is therefore seen that having a dialogic teaching and learning pedagogical method, which caters to learners’ variety is highly required. Being in a technology- equipped epoch, YouTube has been discovered to be such a possible tool to aid learners’ dialogic ability. This paper provides an insight on how YouTube could possibly contribute to the enhancement of the ESL teaching and learning hence produce more learners with communicative skill. It therefore discusses how YouTube may be utilized albeit the challenges faced, in the Malaysian ESL teaching and learning context.